Coanda configured aircraft: a preliminary analytical assessment - Abdul Hamid, Mohd Faisal; Gires, Ezanee; Mohd Harithuddin, Ahmad Salahuddin; Abu Talib, Abd Rahim; Mohd Rafie, Azmin Shakrine; Romli, Fairuz Izzuddin; Harmin, Mohammad Yazdi (Institute of Physics Publishing, 2017)
The interest in the use of flow control for enhanced aerodynamic performance has grown, particularly in the use of jets (continuous, synthetic, pulsed, etc.), compliant surface, vortex-cell, and others. It has been widely documented that these active control concepts can dramatically alter the behaviour of aerodynamic components like airfoils, wings and bodies. In this conjunction, with the present demands of low-cost and efficient flights, the use of Coandă effect as a lift enhancer has attracted a lot of interest. Tangential jets that take advantage of the Coandă effect to closely follow the contours of the body have been considered to be simple and particularly effective. For this case, a large mass of surrounding air can be entrained, hence amplifying the circulation. In an effort to optimize the aerodynamic performance of an aircraft, such effect will be critically reviewed by taking advantage of recent progress. For this purpose, in this study, the design of a Coandă-configured aircraft wing will be mathematically idealized and modelled as a two-dimensional flow problem.